Tratamento de esgoto sanitário de baixa carga utilizando reator compartimentado anaeróbio/aeróbio em escala piloto - Silva, Julliana Alves da [UNESP]; Silva, Gustavo Henrique Ribeiro da [UNESP]; Sarti, Arnaldo [UNESP] (FapUNIFESP (SciELO), 2017)
The research’s main goal was to evaluate the treatment potential of low-strength sanitary sewage in an anaerobic/aerobic baffled reactor (AABR) at pilot-scale. The reactor, maintained at room temperature (27ºC to 30ºC), was deployed at Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP), campus Bauru (SP, Brazil), and treated sanitary sewage with organic charge between 0.06 and 0.61 kgCOD.d-1. The AABR was composed by four chambers, physically separated, being the first three chambers anaerobic and the forth chamber aerobic, followed by a settling tank. The monitoration was done during 203 days for the hydraulic retention times (HRT) of 33, 22, 16.5 and 8.25 hours. During the experimental period, it was verified in the whole system a chemical oxygen demand (COD) removal between 71 and 82%, with high removal rates in the anaerobic phase between 62 and 71%. In terms of total suspended solids (TSS), the reactor reached average removal around 90%. The progress reached with this research allowed to present a low cost biotechnological alternative, with the propose of solving the sewage demand derived from small urban and rural communities, and also making possible the reuse of the treated effluent.
Treatment of low-strength sanitary sewage using an anaerobic/aerobic baffled reactor in pilot scale
Keywords: Baffled reactor; Biological treatment; Organic charge; Sanitary sewage